Genetic mutation and tumor microbiota determine heterogenicity of tumor immune signature: Evidence from gastric and colorectal synchronous cancers - Yang, Weili; Zhao, Yaxing; Ge, Qiongxiang; Wang, Xiaoli; Jing, Yang; Zhao, Jingwen; Liu, Gang; Huang, He; Cheng, Fei; Wang, Xiaoxi; Ye, Yulin; Song, Wenjing; et al. (Frontiers in Immunology, 2022)
Both colorectal and gastric cancer are lethal solid-tumor malignancies, leading to the majority of cancer-associated death worldwide. Although colorectal cancer (CRC) and gastric cancer (GC) share many similarities, the prognosis and drug response of CRC and GC are different. However, determinants for such differences have not been elucidated. To avoid genetic background variance, we performed multi-omics analysis, including single-cell RNA sequencing, whole-exome sequencing, and microbiome sequencing, to dissect the tumor microenvironment of synchronous primary tumors of GC and CRC. We found cellular components of juxta-tumoral sites were quite similar, while tumoral cellular components were specific to the tumoral sites. In addition, the mutational landscape and microbiome contributed to the distinct TME cellular components. Overall, we found different prognoses and drug responses of GC and CRC were mainly due to the distinct TME determined by mutational landscape and microbiome components.